Modern problems of creation of complex information and control real time systems - Недайбида, Юрий Петрович; Котова, Юлия Валентиновна; Хлапонин, Юрий Иванович (Ukrainian Information Security Research Journal, 2012)
The article contains the problems of creation of complex information and control real time systems with consideration of the psychical features of man as subject of management. The approach noted in the article gives a possibility for situational assessment of conflicts and bifurcations in complex information and control systems, clearly defined management functions, actions and decision-making between the operator and the technical devices in real time.